Unravelling the oxygen isotope signal (δ18O) of rodent teeth from northeastern Iberia, and implications for past climate reconstructions. (15th August 2019) - Fernández-García, Mónica; Royer, Aurélien; López-García, Juan Manuel; Bennàsar, Maria; Goedert, Jean; Fourel, François; Julien, Marie-Anne; Bañuls-Cardona, Sandra; Rodríguez-Hidalgo, Antonio; Vallverdú, Josep; Lécuyer, Christophe
Abstract: Small mammals, especially rodents, constitute valuable proxies for continental Quaternary environments at a regional and local scale. Recent studies have demonstrated the relation between the stable oxygen isotope composition of the biogenic phosphate from rodent teeth (δ 18 Op ), and the oxygen isotope composition of meteoric waters (δ 18 Omw ), which is related to air temperatures at mid and high latitudes. This work explores the δ 18 Op of rodent tooth enamel (from Murinae and Arvicolinae subfamilies) to investigate the palaeoenvironmental conditions in northeastern Iberia during Marine Isotope Stage 3 (MIS 3; ca. 60-30 ka). Fourteen new δ 18 Op analyses from modern samples in conjunction with forty-six δ 18 Op analyses previously published are used to decipher the isotope record of present-day rodent teeth in this region. Two main factors should be considered in Iberian palaeoenvironmental reconstructions: the singular nature of Iberian δ 18 Omw records and the potential seasonality bias of small-mammal accumulation. Methodological proposals are made with a view to ensuring the correct interpretation of the δ 18 Op of small mammals in reconstructing past air temperatures. This methodology is applied to the MIS 3 sequence of the Cova dels Xaragalls site (Vimbodí-Poblet, Tarragona, Spain), where fifty-one δ 18 O analyses were performed on wood mouse ( Apodemus sylvaticus ) lower incisors. A spring-early summer accumulation of small mammals is suggested for the layers at Cova dels Xaragalls. In agreement with previous environmental studies of the site, variations in the δ 18 Op values suggest slight fluctuations in the climatic conditions throughout the sequence, which are consistent with the stadial-interstadial alternations that characterized MIS 3. Complementary palaeoenvironmental methods determine cooler conditions than nowadays, but within a globally stable climatic period. Highlights: Oxygen isotopes analyses on rodent contributes to continental environment knowledge. Iberia requires a specific regional equation for past temperatures estimation. Prey-predator interactions influence oxygen isotope temporal information recorded. Seasonality bias and Iberian context are considered in the methodological proposal. Complementary palaeoenvironmental methods yielded matching results at Xaragalls cave.